2023
DOI: 10.3390/v15102018
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of IL-6 Production Induced by SARS-CoV-2 Nucleocapsid Protein and Bangladeshi COVID-19 Patients’ Sera

Abu Hasan,
Rummana Rahim,
Emi E. Nakayama
et al.

Abstract: Coronavirus disease 2019 (COVID-19) is a respiratory tract infection caused by severe acute respiratory syndrome coronavirus 2 that can have detrimental effects on multiple organs and accelerate patient mortality. This study, which encompassed 130 confirmed COVID-19 patients who were assessed at three different time points (i.e., 3, 7, and 12 days) after the onset of symptoms, investigated interleukin-6 (IL-6) enhancement induced by a viral nucleocapsid (N) protein from a myeloid cell line. Disease severity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
1
1
Order By: Relevance
“…On the other hand, the N protein transfection induces a huge rise in the levels of IL-6, IL-12, IL-1β, and TNF-α cytokines. It should be noted that increments in the cytokine levels upon the protein transfection in this study were much higher than other related research (compared to the corresponding controls) 20 , 44 .…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…On the other hand, the N protein transfection induces a huge rise in the levels of IL-6, IL-12, IL-1β, and TNF-α cytokines. It should be noted that increments in the cytokine levels upon the protein transfection in this study were much higher than other related research (compared to the corresponding controls) 20 , 44 .…”
Section: Discussioncontrasting
confidence: 69%
“…Several studies have shown that cytokine levels rise after infection with SARS-CoV-2. Based on the Hasan et al’s study, IL-6 production was enhanced in patient sera upon incubation with a commercially available N protein 44 . According to Wang et al, lung epithelial A549 cells released different cytokines in response to the N protein, rather than the S protein 20 .…”
Section: Discussionmentioning
confidence: 99%